2012
DOI: 10.1007/s12272-012-0112-0
|View full text |Cite
|
Sign up to set email alerts
|

Ethosomes, binary ethosomes and transfersomes of terbinafine hydrochloride: A comparative study

Abstract: The aim of this study was to compare the skin permeation of liposomes, transfersomes and ethosomes of lamivudine under non-occlusive conditions. The liposome and transfersomes prepared by thin film hydration method and ethosomes were prepared by slight modification on hot method. The Liposomal formulation (LP1) ethosomal formulation (ET2) and transfersomal (TF2) formulation showed highest entrapment 49.76 ± 2.1%, 81.97 ± 1.5% and 83.81 ± 1.4%, optimal nanometric size range 515 ± 4.6 nm, 374 ± 8.9nm and 315 ± 8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
53
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 85 publications
(54 citation statements)
references
References 33 publications
1
53
0
Order By: Relevance
“…Significant decrease in particle size from 103.7±0.9 nm to 76.3±0.5 nm was achieved when PG concentration was increased from 0% to 20% v/v. 13 Zhou et al observed that the entrapment efficiency of sophoridine, matrine, sophocarpine, and lehmanine extracted from Sophora alopecuroides increased significantly when PG was incorporated into the ethosomal system with a ratio of ethanol to PG of 1:1 (total alcohol 45%). 11 Other researchers have suggested that the presence of ethanol and PG in ethosomes provides better solubility of drugs, and hence higher entrapment efficiency and improved drug distribution throughout the vesicle.…”
Section: Propylene Glycolmentioning
confidence: 99%
See 4 more Smart Citations
“…Significant decrease in particle size from 103.7±0.9 nm to 76.3±0.5 nm was achieved when PG concentration was increased from 0% to 20% v/v. 13 Zhou et al observed that the entrapment efficiency of sophoridine, matrine, sophocarpine, and lehmanine extracted from Sophora alopecuroides increased significantly when PG was incorporated into the ethosomal system with a ratio of ethanol to PG of 1:1 (total alcohol 45%). 11 Other researchers have suggested that the presence of ethanol and PG in ethosomes provides better solubility of drugs, and hence higher entrapment efficiency and improved drug distribution throughout the vesicle.…”
Section: Propylene Glycolmentioning
confidence: 99%
“…64 It was introduced by Touitou in 1996, 5 and involves the preparation of the organic phase and aqueous phase separately. The organic phase is obtained by dissolving the phospholipids (in addition to surfactants or penetration enhancer for transethosomes) in ethanol or mixture of solvents (ethanol/PG) for the preparation of binary ethosomes, 13 at room temperature, 73 or at 30°C. 6 The aqueous phase used is either water, 44,74,75 buffer solution, 76,77 or normal saline solution.…”
Section: Preparation Techniques and Their Effects On Ethosomal Propermentioning
confidence: 99%
See 3 more Smart Citations